Training of students for entrepreneurial activity in a system of Ukraine’s VET - Aistrakhanov, Dmytro (Professional Pedagogics, 2012)
The work under study is a result of information-analytical review of different official sources con- cerning electronic resources (sites of information centers, vocational schools, libraries etc) on problems of vocational schools students training for entrepreneurial activity. Tasks that are set before teachers by the state require persistent and more effective both theoretical and practical scientific-pedagogical activity for their successful implementation in a real life of studying youth. The author analyzes tasks, modern state of works and theoretical problems of vocational schools students training for entrepreneurial activity.